Moral value of smart hafiz toys for children worship series with the title â€œdonâ€Ÿt lieâ€ - Salamah Salamah; Idawati Idawati; Bastian Sugandi (Universitas Muhammadiyah Surabaya, 2020)
Abstract This research was conducted to determine the moral values contained in SmartHafiz. The are several components contained in Smart Hafizincluding pre schoolanimation, educational animation, Diva the series, movies, worship series, ahlakpraiseworthy, 30 juz, asmaulhusna, little child, 44 sing a song, and your body. Smart Hafiz series of worship sessions